Studi Literatur: Tanaman Herbal Indonesia yang Berkhasiat sebagai Penurun Hipertensi - suci Wahyuni (Program Studi S1 Farmasi, STIKES Senior, Medan, 2023)
Introduction: Hypertension or what is often referred to as high blood pressure is a degenerative disease or PTM that often appears without symptoms. Hypertension is a disturbance in blood circulation that can be life- threatening for individuals when blood pressure is above systolic and diastolic pressure which is unstable. Other hypertension treatments can use good herbal plants to treat various diseases. Various kinds of active substance components which have been widely studied have therapeutic effects derived from herbal plants. About 75- 80% of the worlds population, especially in developing countries, use herbal medicines for primary health care because of their better acceptance of the human body. Objective of the research: The purpose of this literature review is to find out the nutritious herbal plants in Indonesia as traditional medicines to reduce hypertension. Method: The method used in writing this article is a literature review approach by searching literature using the Google Schoolar website database. Result: The results of the study found 15 plants as herbal medicines as drugs to reduce hypertension, namely celery leaves (Apium graveolens L), ginger (Zingiber officinale), basil leaves (Ocimum basilicum), Moringa leaves (Moringa oleifera), garlic (Allium sativum), Turmeric (Curcuma longa), butterfly pea flower (Clitoriaternatea), papaya leaves (Carica papaya), betel leaves (Piper Betle Linn), cucumber (Cucumis sativus), gotu kola leaves (Centella asiatica), carrots (Daucus carota L), bay leaves (Syzygium polyanthum), meniran leaves (Phytallantus niruri), soursop leaves (Annona muricata Linn). Conclusion: Traditional medicine using herbal plants is believed to be able to treat hypertension which has been part of public belief from time to time. The utilization of these traditional plants takes into account aspects such as ease of obtaining, saving costs, and not containing chemicals that cause other side effects.